Comprehensive analysis of E-learning systems compatibility and solutions - Makowski, Tomasz; Sakowicz, Bartosz; Wojtera, Michał (Видавництво Львівської політехніки, 2010)
The aim of the research presented in this paper was to analyze different e-learning solutions and compare them in the field of functionality and standards compatibility. As most popular applications Moodle, WBT and EXE programs have been chosen. The possibility of export/import courses between them has been discussed.
Keywords: e-learning; SCORM; Moodle; WBT; EXE